RANCANG BANGUN ALAT PERAJANG UBI KAYU DENGAN TRANSMISI PULI DAN SABUK PADA PUTARAN MOTOR LISTRIK 1400 RPM DAN DAYA MOTOR 0,5 HP - Anwar, Irwan; Afdal, Afdal; Wardianto, Dedi (ITP Press, 2024)
Cassava is one of a growing food commodity today, the perpetrators were racing home industry to produce cassava-based foods are diverse. In the process of its managing society many still use the traditional way. The process of working with the traditional way gives less satisfactory results because of low productivity, therefore the authors are trying to develop a device capable of producing sweet chopper effective and efficient productivity. Tool chopper cassava with transmission pulleys and belts on electric motor rotation 1400 rpm and 0.5 hp motor power, capable of generate the cutting capacity up to 66 kg / hr. This sweet chopper tool has two blades that the bolts on the disc blades, disc with angular velocity 73 rad / s and the force in the result by a disk of 24.56 N. Round of 700 rpm drive pulleys with a reduction ratio of 2. Materials used are pulleys FC30 and belt types used are belt type A, with a shaft diameter of 12 mm and the shaft is in motion the 15 mm. Bearings used are bearing 6202. The tool has a grounding chopper yam piece with sisitem spring press, which can minimize the accident rate.